Recovering Celtic Spirituality: Semiotics and The Navigatio sancti Brendani abbatis - Walker, Maxine E. (Journal of the Irish Society for the Academic Study of Religions, 2017)
To explore an aspect of the contemporary quest to recover ‘Celtic spirituality’ and to locate sacred landscapes, this paper examines the sea journey of sixth-century St. Brendan and his fellow monks to various islands in the North Atlantic. In speaking the language of the monastery on the islands, St. Brendan reads and interprets the experiences on these islands not as ‘sacred’ but as a context in which the monastic family continues its rituals. Using St. Brendan’s identification of the unknown-sign ‘whale’ with the known-sign ‘island,’ studies in semiotics and sign-theories discover the complications in recovering ‘Celtic spirituality’. Postmodern fragmentation and cultural discontinuities seem to make such a recovery impossible, but notions of viewing the ‘other’ as a part of oneself may locate ways to set out again on an open sea toward ‘island’.